DEVELOPMENT OF IRRIGATION SYSTEMS IN THE MIDDLE AGES - Mamadaminova Bakhtigul Abdupattaevna; Alimukhammedova Nodira Yadgarovna (Scholar Express Journal, 2023)
Central Asia was the one of the cultural developing continent from the history. As the results of the invasions, the existing irrigation systems in the country broke down, which led to the depression of artificial irrigation farming. This article discusses the influence of the history the irrigation system on the socioeconomic development of the country in the Middle Ages
Keywords: Central Asia; irrigated farming culture; irrigation